Potential of Medicinal Plants in Indonesian Forest Biodiversity Conservation in Synergy with Pharmaceutical Technology for Modern Medicine - Hasyim, Dadang Muhammad; Anurogo, Dito; Bansaleng, Yessikah Feiby; Hiola, Siti Fatmah; Anripa, Nuralfin (Malikussaleh University, Aceh, Indonesia, 2025)
This study aims to identify challenges and opportunities for medicinal plant conservation in Indonesian forests, focusing on local communities' role, technology use, and government policies. Indonesia's forests, rich in medicinal plants, face grave threats from deforestation and land conversion for agriculture. Climate change is also exacerbating the sustainability of medicinal plants by changing their growth patterns. Local communities living around forest areas have traditional knowledge that is critical to the conservation of medicinal plants. If properly utilized, this knowledge can help maintain the sustainability of medicinal plant species and minimize the negative impacts of land conversion. In addition, information technology and biotechnology offer solutions for monitoring and preserving medicinal plants. Mapping and active compound extraction technologies can improve conservation quality and facilitate the development of medicinal plant-based products for modern medicine. However, a significant challenge faced is the lack of policies that support medicinal plant conservation and the lack of clarity in regulations governing the utilization of these plants. Community empowerment through conservation education and training is key to the long-term success of medicinal plant conservation. By integrating the community's traditional knowledge, supportive policies, and modern technology, medicinal plant conservation can be carried out sustainably. This research emphasizes the importance of collaboration between the government, local communities, and the private sector in achieving conservation goals that are more effective and beneficial for all parties.